Description of Two new Species of Indo-Pacific Thylacoplethus and a New Record of Thompsonia Japonica (Rhizocephala: Akentrogonida: Thompsoniidae) from Hermit, Porcelain, and Mud Crabs (Decapoda) Based on Morphological and Molecular Data. Issue 2 (1st March 2015) - Hiller, Alexandra; Williams, Jason D.; Boyko, Christopher B.
Abstract: Rhizocephalans of the order Akentrogonida are parasitic barnacles that infest decapods, stomatopods, peracarids, and other cirripedes. Within this order, Thompsoniidae is found in decapods and stomatopods, and is a family comprised of species characterized by having multiple globular reproductive bodies (externae) erupting from the host's extremities and abdominal surface, and connected internally by a root-like system. Two of the four genera currently accepted within Thompsoniidae, Thompsonia and Thylacoplethus, contain perhaps the most morphologically derived species within Akentrogonida. Herein we describe two new species of Thylacoplethus, T. porcellanus and T. umanguvatus, from the porcellanid and hermit crabs Petrolisthes scabriculus (Dana, 1852 ) and Calcinus morgani Rahayu and Forest, 1999, respectively. We also redescribe Thompsonia japonica Häfele, 1911 from a xanthid brachyuran crab based on morphological characters and DNA sequences of the nuclear 18S rDNA gene. The new species from the porcellanid crab comprises the first record of an akentrogonid rhizocephalan parasitizing a species of Porcellanidae. We reconstruct a molecular phylogeny of Akentrogonida using new and published DNA sequences, and we discuss our findings within an evolutionary context of host speciation. All species in the four thompsoniid genera are briefly reviewed, and a replacement name is proposed for the preoccupied Pottsia Høeg and Lützen, 1993 .